(Invited) Investigations and Improvements of AlInN/GaN HEMTs Grown on Si. (13th April 2015) - Chyi, Jen-Inn; Hsin, Yue-Ming; Lee, Geng-Yen; Chiu, Hsien-Chin
Abstract : This paper reports our continuous efforts and achievements in understanding and improving AlInN/AlN/GaN heterostructure for high performance field-effect transistors and switching devices. AlInN/AlN/GaN high electron mobility transistors (HEMTs) with high electron mobility and low sheet resistance have been demonstrated on 6" Si(111) substrates. It is found that electron mobility of AlInN/AlN/GaN HEMTs is closely related to the presence and quality of the AlN spacer layer, which determines the dominant carrier scattering mechanism. A comparative study on the electrical characteristics of AlInN/AlN/GaN and AlGaN/GaN metal-insulator-semiconductor (MIS)-HEMTs shows that both devices exhibit similar low-frequency noise behavior and no obvious generation–recombination (g–r) noise component, implying carrier number fluctuation is the dominant noise mechanism in both structures.